REPRESENTASI DISFUNGSI KELUARGA DALAM FILM НЕЛЮБОВЬ (NELYUBOV’): Representation of Family Dysfunction in the Film Nelyubov’ - Marsya Faiha; Mochamad Aviandy (Jurnal Bastra (Bahasa dan Sastra), 2025)
Families that are unable to solve their problems and fulfill their obligations are called dysfunctional families. One of the real forms of dysfunctional families is divorce. Russia had the highest divorce rate in the world. This research aims to understand how family dysfunction is represented in the movie Нелюбовь (Nelyubov'). The review was conducted based on Donna F. LaMar's characteristics of dysfunctional families using Stuart Hall's Representation theory and and qualitative descriptive method. The research indicates that there are five main indicators of family dysfunction in the film Nelyubov’. These are: the absence or poor quality of interaction between family members; the failure to meet the individual needs of family members; the absence of clear values within the family; various forms of abuse and neglect; and the deep disruption of family responsibilities.